2020
DOI: 10.1186/s12879-020-4808-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural polymorphisms in HIV-1 CRF01_AE strain and profile of acquired drug resistance mutations in a long-term combination treatment cohort in northeastern China

Abstract: Background: The impacts of genetic polymorphisms on drug resistance mutations (DRMs) among various HIV-1 subtypes have long been debated. In this study, we aimed to analyze the natural polymorphisms and acquired DRM profile in HIV-1 CRF01_AE-infected patients in a large first-line antiretroviral therapy (ART) cohort in northeastern China. Methods: The natural polymorphisms of CRF01_AE were analyzed in 2034 patients from a long-term ART cohort in northeastern China. The polymorphisms in 105 treatment failure (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…3 Nevertheless, treatment outcomes were largely unaffected by the large number of natural polymorphisms found in CRF01_AE. 9 Based on the present results, CRF01_AE was identified as the dominant HIV-1 CRF in Makasar, Indonesia, similar to other regions in Indonesia. In addition, major and minor DRMs conferring resistance to NRTI were frequently found in RT genes derived from ART-experienced subjects.…”
Section: Textsupporting
confidence: 71%
“…3 Nevertheless, treatment outcomes were largely unaffected by the large number of natural polymorphisms found in CRF01_AE. 9 Based on the present results, CRF01_AE was identified as the dominant HIV-1 CRF in Makasar, Indonesia, similar to other regions in Indonesia. In addition, major and minor DRMs conferring resistance to NRTI were frequently found in RT genes derived from ART-experienced subjects.…”
Section: Textsupporting
confidence: 71%
“…cDNA library construction and sequencing were as in our previous study [ 60 ]. Briefly, the PCR products were purified using Agencourt AMPure XP beads (Beckman Coulter, Brea, CA, USA) and quantified using a Qubit 3.0 Fluorometer (Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of NGS-based genotyping in providing numerical data allows it to report the relative abundance of the variants and predict DRMs 5,17,20,21 . Recent studies have demonstrated the importance of identifying patients who are prone to virological failure due to an increasing evidence of LADRMs inducing immune system suppression, drug resistance aggregation, and death 5,[22][23][24] .…”
Section: Introductionmentioning
confidence: 99%